The uprising of May 8, in the Ain -Al-Kabira region through the some living testimonies - bouteba, lakhdar (The Algerian Historical Journal, 2026)
The colonial village of Périgotville (Ain -El-Kabira located 27 km north of Sétif) and its surroundings considered to be one of the areas that had experienced the bloody eighth of May 1945, and was even a hotspots. It is true that the events started in the city of Sétif after the peaceful march turned into violence but quickly spread to the surrounding villages. Where the region had experienced tragic events, those who undergone the experience still remember the horror that spread among the population. In this article, we try to focus on these painful events relying on French official documents on the one hand, and on the other, the testimonies of some of those who experienced these events.